Teachers' Efforts to Improve Politeness Towards Students at SMPN 24 Medan - Siti Mutiah (Al-Ulum: Jurnal Pendidikan Islam, 2023)
The purpose of this study was to determine the teacher's efforts in improving students' polite behavior. This study uses a qualitative approach with phenomenological research methods. The research subjects were students at SMP Negeri 24 Medan with a total of about 30 people. In this study, the informants were taken by purposive sampling. Collecting data using interviews and observation. The results of the study stated that: the forms of teacher efforts to improve student manners at school, namely: religious cultivation, teaching and learning process, punishment, individual and group guidance, and parental involvement.